Cytogenetic study on three species of the genus Triatoma (Heteroptera: Reduviidae) with emphasis on nucleolar organizer regions - Severi-Aguiar, Grasiela Dias de Campos [UNESP]; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (Firenze University Press, 2005)
The use of banding techniques allows the recognition of chromosomal pairs and karyotypical arrangements. However, its application in Heteroptera holocentric chromosomes is limited. Thus, little is known about their structure, specially their Nucleolar Organizer Regions (NORs). A comparative analysis of the nucleolar characteristics present during spermatogenesis in Triatoma platensis, Triatoma protacta and Triatoma tibiamaculata seems to indicate that in this group of insects nucleolar fragmentation occurs after prophase I. The study of chromosomal structure of these triatomines indicates that NORs are located at some telomeric and interstitial autosome regions and at sexual chromosomes (X/X1X2).
Keywords: Holocentric chromosomes; NOR; Nucleolar fragmentation; Silver impregnation; Spermatogenesis; Triatomines; Heteroptera; Hexapoda; Insecta; Reduviidae; Triatoma; Triatoma platensis; Triatoma tibiamaculata